2014
DOI: 10.1620/tjem.232.63
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma of the Internal Auditory Canal Mimicking Vestibular Schwannoma: Case Report and Review of 17 Recent Cases

Abstract: Osteoma of the internal auditory canal (IAC) is an uncommon benign bone tumor. Its imaging features may be similar to other IAC lesions, such as vestibular schwannomas that are benign and usually slow-growing but sometimes life-threatening tumors. Thus, detecting IAC lesions and differentiating osteoma from other IAC lesions are both important clinically. We report a case of misdiagnosis of an IAC osteoma as an IAC schwannoma based on magnetic resonance (MR) imaging using the three-dimensional constructive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…A review of the literature by Suzuki et al (2014) of 17 cases of CAI osteoma identified several clinical features, namely: a mean patient age of 44.1 years (male:44; female:44.2), a female-to-male sex ratio of 1.4:1, bilateral localization for 2 cases. Six cases were identified incidentally (12%), including our case who was asymptomatic on the affected side at detection, 7 cases had subjective or objective hearing loss (41%), 10 cases had tinnitus and/or auditory fullness on the affected side (59%), 11 cases had vertigo and/or dizziness (including medical history) (65%), and 2 cases had facial palsy [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature by Suzuki et al (2014) of 17 cases of CAI osteoma identified several clinical features, namely: a mean patient age of 44.1 years (male:44; female:44.2), a female-to-male sex ratio of 1.4:1, bilateral localization for 2 cases. Six cases were identified incidentally (12%), including our case who was asymptomatic on the affected side at detection, 7 cases had subjective or objective hearing loss (41%), 10 cases had tinnitus and/or auditory fullness on the affected side (59%), 11 cases had vertigo and/or dizziness (including medical history) (65%), and 2 cases had facial palsy [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Osteomlar baş boyun bölgesinde frontal etmoid bölgede, maksiler sinüste, mandibulada nadiren de temporal kemikte izlenir [3,4]. Temporal kemikte olan osteomlar dış kulak yolunda, orta kulakta, akustik kanalda, petröz apekste ve nadiren mastoid kortekste izlenir [ 5,6,7]. Baş boyun bölgesinde olan benin tümörler içerisinde mastoid kemik osteom insidansı % 0.1-1 arasında bildirilmiştir [8].…”
Section: Discussionunclassified
“…Osteomas are slow-growing benign bone tumors commonly observed in the temporal bone, especially in the mastoid cortex and external auditory canal. Its appearance in the IAC is very rare and is usually discovered incidentally [1]. The main differential diagnosis is with Exostosis.…”
Section: Descriptionmentioning
confidence: 99%
“…Unlike the Osteoma, Exostosis usually present with multiple bilateral lesions with a broad implantation base [2]. CT is the most effective diagnostic tool for this type of bone lesions [1].…”
Section: Descriptionmentioning
confidence: 99%